Propuesta de creación de una línea de producción y comercialización, mediante una estrategia de marketing para el mercadeo de una arenilla para felinos domésticos que incorpore el desecho de óxido de magnesio, en la empresa Hebesta S.A.S. (2020)
In this project, was made a proposal, to create a new line of production, that line involve marketing strategy for domestic cat litter, that incorporate waste of magnesium oxidoum, from the company Hebesta S.A.S. by using the knowledge acquired during the Industrial Engineering degree. Initially, for enter through the evaluation of tools such as the PESTAL, where the analysis of IPC and PIB was an important part. In turn, the “cámara de comercio” tool was warned out to a business diagnosis. Subsequently, a marketing study was made where porter’s forces were analyzed, the segmentation help to determinates an existing demand, the supply and the possible competition. Finally, was determinate the execution of a marketing mix where was considered, different kind of strategies to implement inside of Hebesta S.A.S., to enter in the market. On the other hand, a technical study defined the characteristics of the product, the manufacturing standard time, the capacities required, the machines and tools necessary, the requirement material plan, the distribution plant and all the implementation of SST.